Gendered, Sexed, and Traumatized Experiences in Anita Nair’s Cut Like Wound and Eating Wasps - K. Swarnamughi; Manimozhi Sayeekumar (Journal of Psychosexual Health, 2026)
Background: Gender identity, patriarchal oppression, and the pursuit of personal liberation remain central concerns within contemporary Indian literature. Anita Nair’s fiction critically engages with these themes by portraying the lived realities of marginalized individuals and women negotiating rigid societal norms and patriarchal structures. Objective: This study aims to examine the interconnected themes of gender identity, patriarchal control, oppression, and female empowerment in Anita Nair’s novels Cut Like Wound and Eating Wasps , with particular emphasis on their social, cultural, and psychosexual implications. Methods: The research adopts a qualitative and thematic literary analysis of the selected novels. Through close textual reading and interpretative analysis, the study explores representations of gender binaries, identity crises, violence, societal expectations, and women’s resistance within patriarchal social frameworks. Results: The analysis reveals that Cut Like Wound foregrounds the struggles of marginalized individuals confronting gender identity conflicts and patriarchal violence, thereby exposing the intersection of identity, power, and social exclusion. The protagonist’s experiences symbolize resistance against rigid gender binaries deeply embedded in patriarchal society. In contrast, Eating Wasps highlights the emotional, social, and psychological struggles faced by women in small-town India as they navigate societal expectations and pursue personal liberation. Both novels collectively portray women’s resilience, agency, and gradual movement toward empowerment despite oppressive social constraints. Conclusion: Anita Nair’s narratives offer a powerful critique of patriarchal social structures and restrictive gender norms in Indian society. Through new character portrayals and thematic depth, the novels underscore the complexities of gender identity, psychosexual autonomy, and female resistance, while emphasizing the transformative potential of resilience and self-liberation.